The Effectiveness of Interactive Educational YouTube Videos in Developing the Reading Skill of Female Students with Learning Disabilities - Al Momani , Randa Mousa; Al Raqad , Mai Mohammad (Dirasat: Educational Sciences, 2024)
Objectives: The study aimed to reveal the effectiveness of interactive educational YouTube videos in the development of the reading skills among female students with learning disabilities. Methods: The study relied on the quasi-experimental method. The study tools consisted of interactive educational YouTube videos and a reading skill note card, which included (8) reading skill standards. The validity and reliability of the two tools were verified. The study sample consisted of (20) students with learning disabilities in the resource room at a school in Al- Juwayriya Umm al-Mu’minin Basic School for Girls in Amman Governorate. They were distributed into an experimental group consisting of (10) female students, and a control group consisting of (10) female students. The study adopted a three-way Likert scale (excellent, moderate, poor), so that each of the eight skills on the observation card was given a score from (1-3). Results: The results of the study showed statistically significant differences between the two experimental groups and the control on the post-reading skill observation in favour of the experimental group that was taught using interactive educational YouTube videos. Conclusion: The study recommended that YouTube educational videos should be used to develop the reading skill for students with learning disabilities due to their proven effectiveness in teaching, and dedicating educational YouTube channels to teach reading in an interactive, fun and entertaining way for students with learning disabilities in different age levels.